Evaluation of puberty menorrhagia in tertiary care centre - Yadav, Anupama; Kaur, Harvinder; ., Satyender (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Puberty menorrohagia is real trouble among adolescent girls mostly due to problem in hypothalamic-pituitary-ovarian axis. The objective of the study was to evaluation of causes of puberty menorrhagia in tertiary care hospital. Methods: Present study evaluates 60 adolescent girls of age group 11-19 years attending Gynaecology OPD/IPD with excessive Menstrual bleeding who conform to the Inclusion criteria were recruited for the study in the department of Obstetrics and Gynaecology of Deen Dayal Hospital Hari Nagar New Delhi over a period of 1 year (August 2018 to June 2019). Results: Out of 60 patients with puberty menorrohagia 47 had anovulatory DUB, 6 had bleeding disorders, 4 had hypothyroidism and 3 had PCOD. Conclusions: Anovulation caused by immaturity of hypothalamic-pituitary-ovarian axis is the most common cause of puberty menorrhagia.